Discourse Process of Laws on Sexual Violence in Public Sphere - cusdiawan (GoResearch - Research & Publishing House, 2022)
This article discusses the background of the idea of Sexual Violence Crime (TPKS) using a discursive approach. Therefore, what this article shows is the discourse (argument) regarding the importance of the legislation, in addition to discussing the arguments of those who reject the discourse, which has led to a long polemic in the public space. For discourse initiatorsLaw TPKS, the rampant sexual violence against women, and oftentimes the legal process and stigma actually add to the victims' suffering, are the main reasons why a legal umbrella with a perspective is needed. feminist jurisprudence as found in Law the. Meanwhile, for those who reject it, the legislation is considered un-Islamic and non-Pancasilais. Therefore, the discursive approach looks at how these two parties deliberate to produce a consensus. This article also points out the importance of understanding 'constitutional patriotism', so that it is in line with democratic values, and because of this, this article is of the view that it is indeed the right step to legalize the Draft Law to be Law TPKS.